TRANSFORMASI BIROKRASI PUBLIK DI BKKBN PUSAT - Adi Wahyono (Widyariset, 2010)
National Family Planning Coordinating Board (NFPCB) as Non Department Goverment Institution of RI have been facing environtment strategic changing. To arrive at the improvement, among the other methods, is organization transformation toward Learning Organization, where the organization member be able to develope their capacity continuously to reach the optimal result. The Indonesia NFPCB is a public birocracy which has core business and responsible on population policy development, birth control, and family prosperous development. The problemis how learning goes on in the public birocracy, and what are components related to the transformation toward learning organization. Reserach methodology applied interpretative, qualitative approach used phenomenology methods. The results of the research indicates that NFPCB organization is unable in transforming the learning organization. The learning organization is just conceptual framework, or knowledge, it is not an operational organization behavior. Finally the organization deffensive routine activities, unsystemic problem solving, innovationand experiment by applying the new approach are weak. The organization unable to learn from the past NFPCB succeed, which fruitfull on moving the community into the family planning programmes. The existance of having a new leader always there is a new hope that the NFPCB will arrived at the same succes as it is in the past. It isrecommended to internalize culture values of the organization to the whole organization member, and the leader should be able to revised the system to push all organization member to learn faster on increasing their capacity to face the strategyc environment changes.